Weak KAM theorem for Hamilton‐Jacobi equations with Neumann boundary conditions on noncompact manifolds. (28th November 2014) - Kong, Yuedong; Xu, Junxiang
<x xml:space="preserve">Abstract</x> In this paper, we consider Hamilton–Jacobi equations with homogeneous Neumann boundary condition. We establish some results on noncompact manifold with homogeneous Neumann boundary conditions in view of weak Kolmogorov‐Arnold‐Moser (KAM) theory, which is a generalization of the results obtained by Fathi under the non‐bounded condition. Copyright © 2014 John Wiley & Sons, Ltd.